Liberation of accessory minerals from various rock types by electric-pulse disintegration: method and application - B. E. Burakov; S. D. Lupal; O. A. R. Thalhammer; B. Saini-Eidukat (The Institute of Materials, Minerals and Mining, 1995)
Electric-pulse disintegration is a mineral separation technique that liberates all mineral grains from any igneous or metamorphic rock irrespective of its lithology or grain-size distribution. The normal mechanical crushing of whole-rock samples is replaced by the rending effect of an explosion, produced by applying an electric current from a high-voltage power source. A voltage greater than the 100 kV necessary for the electrical breakdown of rock samples is achieved by using capacitors charged in parallel, but discharged in series. The sample sits in a water bath and the rapid distribution of electric pulses leads to an explosion which occurs preferentially along grain boundaries of the sample. Individual, undamaged mineral grains can be recovered in their original shape and form regardless of grain size. Examples are given of the liberation and concentration of important accessory minerals from different rock types. The examples show the recovery of diamond from two types of non-kimberlitic host rock in Popigai and Kumdykol in Kazakhstan and platinum group minerals associated with chromitites from the Konjdor intrusion and sulphides from intrusions in the Kola Peninsula in Russia